Coexistence effect of rotifer, Brachionus rotundiformis and copepod, Oithona similis in culture media on growth performance and eggs production - Suminto Suminto; Diana Chilmawati (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Suminto, Chilmawati D. 2019. Coexistence effect of rotifer, Brachionus rotundiformis and copepod, Oithona similis in culture media on growth performance and eggs production. Biodiversitas 20: 2396-2402. The effect of Brachionus rotundiformis, and Oithonasimilis coexistence in culture media on the growth performance and egg production were examined and it aims to know the best coexistence percentage which provides the highest growth performance and egg production of O. similis and B. rotundiformis. Experiment method was carried out in this research by using a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments were percentage through mix culture ratio of O.similis. and B. rotundiformis whereas those treatments were with ratio of 100% and 0% (A); 90% and 10% (B); 80% and 20% (C); 70% and 30% (D); and 60% and 40% (E), respectively. The results showed that, B. rotundiformis had a significant effect (p <0.05) on final density, population growth rate and eggs production of Oithona sp.; coexistence of 60% Oithona sp. and 40% B. rotundiformis provides the best final density for Oithona sp. (27.40±0.34 ind./ml) and B. rotundiformis (30.23±0.21 ind./ml); the highest population growth rate of Oithona sp. (0.29±0.02 ind./day) and B. rotundiformis (0.36±0.03 ind./day); and the highest egg production of Oithona sp. (18.83±0.76 eggs/ind) and B. rotundiformis (3.30±0.24 eggs/ind.). However, the mix culture of O.similis. and B. Rotundiformis may be applied in co-existent semi-mass or mass culture.